Empowering Problem-Solving Abilities and Self-Esteem in Students: Implementing the Teams Games Tournament (TGT) Model in Class VIII of MTS Daar Al-Ilmi - Islamiyah, Izzatul; Nasrullah, Anton; Yendra, Novi; Ratnasari, Silvia; Khan, Haider Ali (EDUPEDIA Publisher, 2024)
This study aims to analyze the effect of the Teams Games Tournament (TGT) type cooperative learning model on students' problem-solving ability and self-confidence. This research is a quantitative research using quasi-experimental methods. The research design used is nonequivalent control group design. The research design used is nonequivalent control group design. The stages of this study, namely 1) conducting pretests, 2) providing learning treatment, 3) conducting posttests and questionnaires and 4) drawing conclusions. This research was carried out in class VIII C and class VIII D MTs Daar Al-Ilmi Academic Year 2023/2024. The instruments of this study are tests and questionnaires. This test instrument is in the form of a posttest that measures students' mathematical problem-solving abilities and this questionnaire is in the form of a statement to find out students' mathematical confidence. The results showed that students' mathematical problem-solving ability and mathematical self-confidence of students who received the Teams Games Tournament (TGT) type learning model treatment had an average score of 84.27 Better than the mathematical problem solving ability of students who obtained conventional learning model treatment with an average score of 80.28. So it can be implied that there is an influence of the Teams Games Tournament (TGT) model on students' problem-solving abilities and students' self-confidence is proven.